Living Arrangements of Widowed Elderly Women and their Differentials: A Study in an Urban Setting of Tamil Nadu, India - Singh, Neelu (Journal of Management and Science, 2012)
Living arrangements in the twilight of life is a matter of primary concern for elderly widowed women. In view of this, an attempt is made to examine the effect of background characteristics on the living arrangements of the widowed elderly women making use of the data collected from 330 elderly widowed women from Coimbatore city, Tamil Nadu with frequency and cross-tabular analyses as well as chi-square test of significance. The study found that slightly less than three-tenths of widowed women are „old-old‟ (75+ years). On the other hand, three-fifths of elderly belonged to most backward / backward caste and majority (63%) of them illiterates. About two-fifths (42%) of the elderly widowed women are living with married son. The differentials of elderly living alone vs with children are mostly in expected direction and highly significant (p<0.001) with an increase in the number of earning members in the family, number of children living in the same area / city as well as those who belonged to the households of high standard of living. On the other hand, the percentage of widowed elderly who live alone has shown a clear increasing pattern with an increase in occupational status and instrumental activities of daily living scale. Further, it is noticed that the elderly who are living alone is higher among those who are feeling „unhealthy‟ as compared to those elderly widowed women as „healthy‟. All these percentage differentials are also turned out as significant at different levels of extent (p<0.001 or p<0.05).Based on these findings a few policy implications have been postulated.